Fabrication of Oregano-Olive Oil Loaded PVA/Chitosan Nanoparticles via Electrospraying Method - Vehapi, Meyrem; Yilmaz, Azime; Ozcimen, Didem (TAYLOR & FRANCIS INC, 2021)
Recently, a large number of studies on new methods has\been carried out to increase the antimicrobial activity of bioactive compounds in essential oils. One of the most effective ways is to encapsulate them within some polymer matrix for preservation and extending their bioactive properties. This study appears to be the first attempt to fabricate oregano-olive oil-loaded nanoparticles for increasing bioactive properties. In this study, mixtures of polyvinyl alcohol (PVA) and chitosan were electrosprayed to obtain polymeric nanoparticles in which a mixture of oregano-olive oil was encapsulated. The electrospraying parameters were optimized under static conditions. The fabricated nanoparticles were characterized in terms of their molecular, thermal, and bioactive properties. Antifungal activity of the nanoparticles was tested against some fungal pathogens;Colletotrichum gloeosporioides, Botrytis cinerea, Penicillium chrysogenum. Antioxidant activity of the olive oil, oregano essential oil, and oil-loaded nanoparticles was determined according to 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging method. The results of this study indicated that oil-loaded nanoparticles have a potential to be used as an antimicrobial agent in food preservation applications.
Keywords: Oregano oil; olive oil; electrospraying; nanoparticles; antifungal activity; antioxidant activity; L. ESSENTIAL OIL; PLANT ESSENTIAL OILS; IN-VITRO; ANTIOXIDANT ACTIVITIES; BOTRYTIS-CINEREA; DELIVERY; ANTIBACTERIAL; DISEASES; SURFACE; LEMON; Materials Science